Patriarchal Dominance and Domestic Violence: A Family Law Perspective in North Aceh - Dedi Rismayadi; Alimuddin Alimuddin; Riza Afrian Mustaqim; Zulhilmi Bin Paidi; Zinah Younus (An-Nisa: Journal of Islamic Family Law, 2025)
This paper examines patriarchal dominance as a driving factor of domestic violence, the focus of research in this paper is on gender inequality, violence and infidelity from the perspective of positive law and Islamic family law, experienced by one family in Aceh. The problem of gender inequality has been going on for a long time. Gender inequality is still a concern in developed and developing countries around the world, and this contributes to the increasing practice of discrimination against vulnerable groups, especially women. Indonesia's patriarchal culture was brought from the colonial state. Therefore, women often experience discrimination in society in various ways. Research files (field approach) from Cot Matahe, Syamtalira Bayu District, North Aceh Regency, were used to collect data in this paper using qualitative research methodology. This study focuses on the perspective Through the conflict perspective of the multidimensional approach used to review this issue, it can be concluded that patriarchal culture is one of the major factors in the many discriminatory treatments against women to date, which are mostly dominated by men.